Fibrinolytic Enzyme System and Pregnancy. Issue 5667 (16th August 1969) - Bonnar, John; McNicol, G. P.; Douglas, A. S.
Abstract : The effect of pregnancy on the components of the fibrinolytic enzyme system was determined by serial observations on 10 healthy women during normal pregnancy, labour, and the puerperium. The plasminogen level was substantially increased in the third trimester; the increase occurred pari passu with a pronounced increase in fibrinogen concentration. After allowing for the expansion of plasma volume in pregnancy a twofold increase in the absolute amounts of circulating fibrinogen and plasminogen was found. In late pregnancy and during labour the level of plasminogen activator was greatly decreased, whereas a normal or increased level was present in the first week of the puerperium. No alteration in the levels of inhibitors of plasminogen activation by urokinase was found during normal pregnancy. The thrombin time and platelet count remained unchanged during pregnancy and labour but the platelet count rose significantly during the first week of the puerperium. The haemostatic mechanism in pregnancy appears to be altered towards an enhanced capacity to form fibrin and a diminished ability to lyse fibrin. These changes may be a physiological development to ensure the integrity of the foetal and maternal circulations and provide rapid and effective haemostasis in the uterus during and after placental separation. Nevertheless, the changes may also establish a vulnerable state for intravascular fibrin deposition.